TINGKAT KESULITAN GURU PROGRAM KEAHLIAN TEKNIK BANGUNAN SMK N 1 PADANG DALAM MENYIAPKAN PERANGKAT PEMBELAJARAN KURIKULUM 2013 - 836-846 , Wandesfri Wahyuni (Universitas Negeri Padang, 2015)
ABSTRACT The aim of this study was to know the level of teachers’ difficulty in preparing learning material especially the lesson plan for 2013 curriculum. The design of the research is descriptive research. The population of this research is 21 Engineering teachers at SMK N 1 Padang, the sample is of 17 teachers that were taken by purposive sampling technique. Data were collected using a questionnaire with Likert scale that used four answer choices for positive and negative statements. The numbers of statements in the questionnaire were 55 point statement. The results showed that in preparing the lesson plan (RPP) the teachers had high level of difficulty. Every indicator in preparing a learning material showed the result as followed: 1) The Formulation of indicators was in high difficulty level category; 2) The Formulation of the goal of teaching was in difficulty level category; 3) The selection of the teaching material was in high difficulty level category; 4) the Selection of teaching method was in high difficulty level category; 5)The Selection of media was in high difficulty level category; 6) The Development of learning process was in very high difficulty level; 7) attitude evaluation was very high difficulty level; 8) Ratings knowledge with a high difficulty level category; and 9) Skills evaluation was in high difficulty level. Keywords: Difficulty, Teacher, Curriculum 2013 Learning Materials